Transmission electron microscopical assessment of black cumin fixed oil treatment on rat's hippocampus with surgically induced neurodegeneration - Azzubaidi, Marwan Saad; Talib, Norlelawati A.; Saxena, Anil Kumar; Alattraqchi, Ahmed G.; Maideen, Mohd Maizam (2012)
A growing body of evidence now supports the hypothesis that critically attained threshold cerebral hypoperfusion (CATCH) accelerates age related neurodegeneration. Such threshold was achieved in rats by permanent bilateral common carotid artery occlusion (2VO). The hippocampal CA1 region pyramidal cells are the earliest neurons to degenerate following 2VO intervention. Nigella sativa oil extract (NSO) was found to preserve viability of cerebellar neuron cells in vitro putting forward its potential neuroprotective effect. The study objective was to assess the effect of NSO treatment on hippocampal pyramidal and other neighboring cells within CA1 subfield of rats with CATCH that was achieved through 2VO procedure. Nine rats were equally divided into three groups: sham control, untreated 2VO and NSO treated group (2VO with daily oral NSO treatment). After the 10th postoperative week coronal sections of the hippocampus were collected and processed for transmission electron microscopy (TEM). The neurodegenerative changes observed in pyramidal cells, astrocytes, endothelial basement membrane and axoplasms within CA1 hippocampal region of 2VO group were not observed in sham control group. Meanwhile, NSO treated groups hardly showed ultrastructural neurodegenerative changes similar to those observed in untreated 2VO group. This indicates a promising prospective neuroprotective activity provided by NSO treatment to prevent age related neurodegenerative diseases especially Alzheimer’s disease.